A Novel Multi-focus Image Fusion Method Based on Non-negative Matrix Factorization - Yongxin Zhang; Li Chen; Zhihua Zhao; Jian Jia; Jie Chen (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2014)
In order to efficiently extract the focused regions from the source images and improve the quality of the fused image, this paper presents a novel image fusion scheme with non-negative matrix factorization (NMF). The source images are fused by NMF to construct temporary fused image, whose region homogeneityis used to split the source images into regions.The focused regions are detected and integrated to construct the final fused image. Experimental results demonstrate that the proposedschemeis capable ofefficiently extracting the focused regions and significantly improving the fusion quality compared to other existing fusion methods,in terms of visualand quantitative evaluations.